Impact of human resources in the creative sphere on economic development - Nurbanu Khassenova; Gulsara Mukina; Lyudmila Popp; Saule Kaliyeva; Ardak Turginbayeva; Zhaxat Kenzhin (Problems and Perspectives in Management, 2025)
The industrial era is gradually giving way to a creative economy driven by human resources. This study aimed to assess the impact of human resources within the creative economy on countries’ economic growth. The focus was on human capital involved in the creative economy. Panel data from 21 countries (2016–2023) were analyzed. The ILO classification methodology for employment types was applied. A fixed-effects regression model was employed to assess the impact of human capital on economic growth, while controlling for relevant factors. The model’s coefficient of determination increased from 0.494 to 0.652 with the addition of new variables, indicating improved accuracy. These variables were used to assess the effect of creative economy indicators on GDP per capita across countries. A direct correlation has been established between the share of employed people involved in the creative economy and the country’s level of economic development, specifically in terms of GDP per capita (Gini coefficient: r = –0.431, P = 0.01). The quantitative importance of human resources of the creative economy was calculated for both developed and developing countries of the world. The practical value of the obtained results lies in the possibility of their use for the development of public management decisions to stimulate the economic growth of the country.